Evaluating the impact of electrode planes on regional lung function assessment - Sang, Ling; Sun, Yutao; Lu, Yu; Lin, Zhimin (Frontiers in Physiology, 2024)
Objective The aim of the study was to explore the influence of the measurement plane on regional lung function assessed via electrical impedance tomography (EIT). Methods The forced vital capacity (FVC) maneuver was prospectively performed in 30 healthy male volunteers. Simultaneously, EIT measurements were conducted at the 3rd, 4th, and 5th intercostal spaces (ICS). The EIT-based spirometry parameters are calculated in a similar manner to their original definitions. The spatial and temporal distributions of the corresponding functional images were assessed and compared among the measurement planes. Results All subjects but one were able to perform the FVC maneuver according to the guidelines. Significant differences were found in 67% (6 out of 9) of the EIT-based parameters assessing the spatial and temporal distribution. The fEIT images were most homogeneous at ICS 4 compared to the other two measurement planes, except for the time required for 75% of FVC. The fEIT image FVCEIT distributed toward dorsal regions when the measurement planes moved from ICS 3 to ICS 5, whereas the identified lung areas became smaller. Conclusion The spatial and temporal distribution of the regional lung function measured via EIT was influenced by the measurement planes. We recommend adhering to the same measurement plane for before–after comparison. ICS 4 was recommended for the sitting subjects performing lung function testing.